Aktivitas Antioksidan dengan Metode DPPH dan ABTS Terhadap Ekstrak Etanol Daun Amaranthus hybridus L. - Dewi Ranggaini, Monica; Halim, Johni; Aurelia Tjoe, Michelle (Jurnal Kedokteran Gigi Terpadu, 2024)
Background: Cancer, a degenerative disease, arises from free radicals in the body, which can be counteracted by antioxidants. Amaranthus hybridus L., a vegetable rich in antioxidant compounds like flavonoids, requires extraction to harness these compounds. This extraction uses the maceration technique with 70% ethanol. Antioxidant activity is tested using methods like DPPH and ABTS assays, with the IC50 value indicating effectiveness. Purpose: To determine the difference in antioxidant activity of A. hybridus L. leaves ethanol extract with DPPH and ABTS methods. Method: Laboratory experimental research. Simplicia leaves of A. hybridus L. in 70% ethanol solvent were extracted using maseration method. The antioxidant activity was tested in the sample and the ascorbic acid using DPPH and ABTS methods at wavelenghts 517 nm and 745 nm. Sample absorbance was measured using microplate reader. Result: IC50 values of A. hybridus L. leaves ethanol extract with DPPH and ABTS methods were 54,99 µg/mL and 71,45 µg/mL, for ascorbic acid using DPPH and ABTS methods were 0,62 µg/mL and 3.13 µg/mL. Conclusion: The antioxidant activity of A. hybridus L. leaves ethanol extract with DPPH method has stronger antioxidant than ABTS method.